N6‐Methyladenosine (m6A) readers are dysregulated in renal cell carcinoma. Issue 5 (23rd March 2021) - von Hagen, Felix; Gundert, Larissa; Strick, Alexander; Klümper, Niklas; Schmidt, Doris; Kristiansen, Glen; Tolkach, Yuri; Toma, Marieta; Ritter, Manuel; Ellinger, Jörg
Abstract: N 6 ‐Methyladenosine (m 6 A) is the most common modification of messenger RNA (mRNA) in mammals. It critically influences RNA metabolism and plays an essential role in virtually all types of bioprocesses including gene expression, tissue development, self‐renewal and differentiation of stem cells, stress response and circadian clock control. It plays a crucial role in carcinogenesis and could be used as a prognostic and a diagnostic tool and as a target for new anticancer therapies. m 6 A modification is dynamically and reversibly regulated by three types of proteins. Methyltransferases, so‐called "writers" add a methyl group to the adenosine, which can be removed by demethylases, also called "erasers." m 6 A‐specific RNA‐binding proteins, from here on referred to as "readers, " preferentially bind to the m 6 A site and mediate biological functions, such as translation, splicing or decay of RNA. In this study, we examined the expression of the six m 6 A readers HNRNPA2B1, HNRNPC, YTHDC1 and YTHDF1‐3 in clear cell renal carcinoma (ccRCC). We show that on mRNA level the expression of all six m 6 A readers is significantly downregulated compared to normal renal tissue and on protein level five out of six readers are dysregulated. Lower levels of some m 6 A readers are correlated with advanced stage and grade as well as associated with a shorter overall, progression‐free and cancer‐specific survival. In summary, we could show that m 6 A readers are dysregulated in ccRCC and might therefore act as a tumor marker, could give further information on the individual prognosis and be a target of innovative cancer therapy.